Marrying across Borders in Latin America: Visualizing Intermarriage Flows - Adriana Robles; Luca Maria Pesando; Alejandra Abufhele; Mauricio Bucca; Daniela R. Urbina (Socius, 2024)
The authors propose an adaptation of the well-known “circular plot,” traditionally used to quantify international migration flows, to visualize patterns of intermarriage within Latin American countries. The authors present data on intermarriage flows between partners’ countries of origin using data from recent household surveys from five Latin American countries. The visualization allows an easy-to-grasp snapshot of marital pairings considering partners born in different countries, as well as the identification of their spatial patterns. In some countries, such as Colombia and Peru, most intermarriage occurs between natives and Venezuelans. Conversely, in Chile, Ecuador, and Uruguay, there is much wider heterogeneity in country-pair combinations. In Chile, no country-pair combination dominates, reflecting the more balanced nature of migration flows from a broader set of countries. Overall, the results aid the interpretation of trends and patterns in marriage across country lines by placing them within a comparative regional context. This is a flexible tool that could be easily adapted to multiple other countries within or outside of the region, to analyses over time, and to a heterogeneous array of couple-level characteristics.